Orientia tsutsugamushi modulates p53, the cell cycle, and genotoxicity to maintain its intracellular niche - Paige E. Allen; David L. Armistead; Svetlana Blinova; Jason A. Carlyon (Nature Communications)
Abstract Infections by intracellular pathogens often cause insult to host cell DNA, which stimulates responses that ultimately eliminate the damaged cell and hence the microbial niche. p53 is an innate immunity mediator that responds to DNA damage and intracellular infection by transcriptionally activating pathways that arrest the cell cycle, repair DNA, and elicit apoptosis. How pathogens counter p53 are incompletely understood. Here, we demonstrate that the endotheliotropic obligate intracellular bacterium Orientia tsutsugamushi blocks transcription of TP53 to nearly deplete p53 levels. Contrary to the unrestricted proliferation expected based on the transcriptome of p53-deficient infected cells, Orientia arrests the cell cycle at S phase to promote bacterial replication. It protects host endothelial cells from DNA damage even if induced by etoposide and delays genotoxic-dependent apoptosis until late in infection once a high bacterial load has been achieved. TP53 downregulation, protection against genotoxicity, and inhibition of DNA damage-dependent apoptosis are executed by the Orientia nucleomodulatory effector, Ank13. Therefore, O. tsutsugamushi inhibits TP53 expression and genotoxicity to reconfigure the intracellular environment of its host cell into one that favors bacterial replication.